Development of propolis powder for encapsulation via freeze drying method : purification and freeze drying process of extracted propolis - Enidran, Loganathan (2018)
Propolis or also known as the bee glue is a type of resin which is obtained from bee hives of various bees based their geographical topography. The propolis is known for its various benefits such as antioxidant, antimicrobial, anti-diabetic and anti-imflammatory. In Malaysia, there are 32 types of stingless bee with Trigona Thoracica being mostly found bee species at various parts of the country. However, propolis obtained from the Trigona Thoracica species has a major drawback where it is found to be sticky in normal temperature condition. To address the problem, freeze drying process is carried out. In this study, the water extracted propolis was purified to obtain pure propolis liquid. The purified propolis liquid was then freezed at five different freezing temperatures which were -40°C, -50°C, -60°C, -70°C and -80°C for 48 hours period. The freezed propolis samples were the freezed dried to removed to freezed water and liquid substance for 48 hours period to obtain pure propolis powder. The process was controlled by two parameters, temperature and presure. The obtained powder was then accessed by angle of repose method to determine the flowability and moisture content of the powder samples. Results indicated that the propolis powder sample of -80°C freezing temperature to have the maximum loss in moisture content and the excellent powder flow flowability to be used for encapsulation.